2012
DOI: 10.4236/ojps.2012.23006
|View full text |Cite
|
Sign up to set email alerts
|

Common Origin, Common Power, or Common Life: The Changing Landscape of Nationalisms

Abstract: Socio-territorial psychic constructs, such as national identities, are perhaps the most important psychic phenomena for political science, with their strength so consequential for wars and inter-ethnic conflicts. The construction of the EU has faced scholars and practitioners with two identity-related problems: (i) whether the socio-territorial identities can be conceptualized as being multi-layered (nested, hyphenated, with non-conflictual relationships among the components), and (ii) whether the higher level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…But why is Euroskepticism on the rise when the strength of European identity has not changed? One possible explanation could be that the meaning citizens attach to national and European identity are not taken into consideration in studies that measure national and European identity as a one-dimensional construct, such as attachment (Dennison et al 2020), feeling of belonging (Hooghe and Marks 2004;Koos 2012), or closeness to the nation/the EU (Plescia, Daoust, and Blais 2021). Only few contributions consider what it means for citizens to identify with their nation or with Europe.…”
Section: Forms Of National and European Identity In Europementioning
confidence: 99%
See 2 more Smart Citations
“…But why is Euroskepticism on the rise when the strength of European identity has not changed? One possible explanation could be that the meaning citizens attach to national and European identity are not taken into consideration in studies that measure national and European identity as a one-dimensional construct, such as attachment (Dennison et al 2020), feeling of belonging (Hooghe and Marks 2004;Koos 2012), or closeness to the nation/the EU (Plescia, Daoust, and Blais 2021). Only few contributions consider what it means for citizens to identify with their nation or with Europe.…”
Section: Forms Of National and European Identity In Europementioning
confidence: 99%
“…Although not worded identically, most studies follow the logic of the ethnic-civic dichotomy. Two studies identify a cultural vs civic form distinction (Shulmann 2002;Koos 2012).…”
Section: International Social Survey Programmementioning
confidence: 99%
See 1 more Smart Citation
“…Given that these concepts emerged from the data, I will elaborate on their meanings using the interviewees’ own words. The guidelines also included a section on the political aspect, such as affiliation to Hungary, the Hungarian flag and the national anthem (Koos ). However, this paper only focuses on the cultural aspect and ignores the political one due to methodological limitations and lack of space.…”
Section: Findings Aspects Of Hungarian‐nessmentioning
confidence: 99%
“…Recent relevant literature predominately considers identities as fluid, multidimensional, and personalized social constructions that reflect socio-historical contexts (Howard 2000). It has been suggested that people can hold multiple identities because of their multiple positions in society (Burke and Stets 2009;Chandra 2012;Koos 2012). Moreover, scholars are reaching a consensus that identities can be at once stable and changeable (Howard 2000;Burke and Stets 2009;Chandra 2012;Swayd 2014).…”
Section: Identity and Identification In Normative And Empirical Perspmentioning
confidence: 99%